The action of ginsenoside Rg1 in patients with carotid atherosclerosis: a controlled clinical trial - Fang, Xu; Ma, Xuan; Zhang, Man; Zhang, Li; He, Xu; Liu, Shilei; Dong, Yinsong; Li, Yan; Wu, Junzi (Frontiers in Pharmacology, 2025)
ObjectiveThis study evaluated therapeutic effects of ginsenoside Rg1 (QiShengli Tablets) in patients with carotid artery plaques, in combination with lifestyle interventions, lipid-lowering therapy. We aimed to provide novel insights into safe clinical application of ginsenoside Rg1 for managing cardiovascular and cerebrovascular diseases.MethodsFrom January 2022 to October 2023, 106 carotid artery plaques patients Aged ≥60 and <74 were recruited from the Geriatrics Department of First People’s Hospital of Yunnan Province. All participants provided informed consent and a randomized sequence is generated by random number table method and divided into three groups. Group 1 received lifestyle interventions plus atorvastatin calcium tablets (n = 32). Group 2 received same treatment as Group 1, with the addition of Bayaspirin (n = 33). Group 3 received the same treatment as Group 2, but with Bayaspirin replaced by ginsenoside Rg1 (n = 41). This study adopted a single-blind design: by uniformly encapsulating the tablets in their original form in blind bags, the subjects took them at regular intervals and in fixed quantities There were no significant differences in baseline characteristics among the groups before treatment (P > 0.05). All patients were treated 3 months. Carotid atherosclerosis–related outcomes were assessed after treatment, and data were analyzed using SPSS 24.0.ResultsCarotid ultrasound revealed significant intergroup differences in plaque number and volume changes after treatment (P < 0.05). No significant intergroup differences were observed in arterial stiffness index (P > 0.05). Fibroblast growth factor 21 levels differed significantly among the groups (P < 0.05), whereas Lumican and Fibulin-1 levels did not (P > 0.05). Analysis biochemical indicators revealed significant post-treatment differences in LDL-C, TC, Hcy, IL-6, TNF-α, 25(OH)D, and insulin resistance (IR) (P < 0.05). Notably, after treatment of three groups, Montreal Cognitive Assessment (MoCA) scale score was statistically significant (P < 0.05).ConclusionPatients with carotid atherosclerotic plaques, adding ginsenoside Rg1 to standard therapy reduced the number and volume of carotid plaques. It improved quality of life, decreased specific inflammatory markers, and enhanced blood pressure control and Insulin Resistance (IR). These suggest ginsenoside Rg1 may have clinical value in the future management of carotid atherosclerosis.